2016
DOI: 10.1016/j.jpowsour.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A first-principles study on the effect of oxygen content on the structural and electronic properties of silicon suboxide as anode material for lithium ion batteries

Abstract: Silicon suboxide is currently considered as a unique candidate for lithium ion batteries anode materials due to its considerable capacity. However, no adequate information exist about the role of oxygen content on its performance. To this aim, we used density functional theory to create silicon suboxide matrices of various Si:O ratios and investigated the role of oxygen content on the structural, dynamic, electronic properties and lithiation behavior of the matrices. Our study demonstrates that the O atoms int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…We found that the formation energy of SiO x with relatively low O content (x < 0.5) dramatically increased as oxygen content increased until x = 0.5, at which point it began to decrease. 42,45,47 Si has four valence electrons, requiring four more to fill the octet. At low O content, it is difficult for Si to gain a partial charge from O.…”
Section: Amorphous Silicon Suboxide Structurementioning
confidence: 99%
See 2 more Smart Citations
“…We found that the formation energy of SiO x with relatively low O content (x < 0.5) dramatically increased as oxygen content increased until x = 0.5, at which point it began to decrease. 42,45,47 Si has four valence electrons, requiring four more to fill the octet. At low O content, it is difficult for Si to gain a partial charge from O.…”
Section: Amorphous Silicon Suboxide Structurementioning
confidence: 99%
“…25,42,43 Despite these encouraging developments of Si suboxide anodes, the fundamental understanding of lithiation mechanism of SiO x is still limited, and there have been no experimental or theoretical reports focused on tailoring the oxidation of SiO x for use as an anode. [44][45][46][47][48][49][50] In this study, we investigate the structural stability of SiO x (0 ≤ x ≤ 2) and reaction mechanisms of Li in quartz (SiO 2 ); furthermore, we discuss the structural evolution and voltage profile of Li y SiO x (0 ≤ y ≤ 4) during lithiation using density functional theory (DFT) calculations. The reaction products during lithiation are clarified based on the charge analysis of SiO x .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 However, the inevitable large volume expansion during the cycling process leads to the pulverization of the active materials from the current collector, inhibiting their lifetime. 15,16 To this end, it is necessary to explore and design novel anode materials, which have not only a higher capacity but also a lower volume expansion compared with the conventional graphite anode.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Si, Ge, and Sn‐based alloys with the enhanced gravimetric capacity (theoretical value of Si: 4198 mAh/g, Ge: 1625 mAh/g, and Sn: 994 mAh/g) have been extensively investigated as potential alternatives for LIB anode 13,14 . However, the inevitable large volume expansion during the cycling process leads to the pulverization of the active materials from the current collector, inhibiting their lifetime 15,16 . To this end, it is necessary to explore and design novel anode materials, which have not only a higher capacity but also a lower volume expansion compared with the conventional graphite anode.…”
Section: Introductionmentioning
confidence: 99%